PHYTOTEST ASSESSMENT OF POTENTIAL HEALTH RISKS TO CHILDREN FROM USING SECOND-HAND AND STOCK CLOTHING WASHED WITH SYNTHETIC DETERGENTS - Tkachuk, Nataliia; Koroid, Mariia (Biota. Human. Technology, 2025)
Second-hand clothing, for the treatment of which formaldehyde is used, as well as stock clothing, are widely used in Ukraine. The toxicity of such clothing can be assessed by phytotesting using Lepidium sativum as a test plant. It is proposed to solve the problem of clothing toxicity by washing with synthetic detergents, which include compounds with toxic properties. The aim of this work was to study the toxicity of reusable clothing (“second-hand”) and stock clothing using L. sativum phytotest in different washing options with children’s laundry detergents and to assess the potential health risks to children when using such clothing. Methodology. The study used the method of questioning students about their use of second-hand clothing, as well as the method of phytotesting the toxicity of second-hand clothing and stock clothing washed with synthetic detergents, using Lepidium sativum as a test plant. During the study, 3 series of experiments were carried out. The results were statistically processed. Scientific novelty. For the first time, the toxicity of second-hand children’s clothing and stock clothing after washing with synthetic detergents has been shown in the growth test with Lepidium sativum, which may be associated with residual compounds of these detergents and is potentially dangerous for children’s health. Conclusions. Phytotesting has established a slight toxicity of second-hand and stock cotton clothing, which may be associated with residual compounds used to treat such clothing. The presence of water-soluble and water-insoluble residual compounds after washing such clothing with synthetic detergents ensures its toxicity (from weak to extreme), which is potentially dangerous for the health of children. Elimination of toxicity of second-hand and stock cotton clothing is achieved by washing them with laundry soap.